ANALISIS KANDUNGAN GIZI TERIPANG HITAM (Holothuria edulis) DAN TERIPANG PASIR (Holothuria scabra) DI PERAIRAN PANTAI PURA AGUNG WERI - Dasilva, Theresia Susana; Tukan, Maria Magdalena N.M.; Peni, Donata (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Sea cucumbers are a type of spiny-skinned animal (Echinodermata). The spines on sea cucumbers are a skeleton made of limestone and found within their skin. There are approximately 1,250 species of sea cucumbers that have been described by taxonomists. This study aims to determine the nutritional content of sand sea cucumbers (Holothuria scabra) and black sea cucumbers (Holothuria edulis) in the coastal waters of Pura Agung Weri, East Flores Regency. The study was conducted in the Fisheries Product Technology processing room of the Larantuka Teacher Training and Technology Institute, then an analysis of the nutritional content of black sea cucumbers (Holothuria edulis) and sand sea cucumbers (Holothuria scraba) was carried out which included water content, ash content, protein, fat, and carbohydrates in the Feed Chemistry laboratory of the Faculty of Animal Husbandry and Marine Sciences at UNDANA. The water content and ash content tests used the gravimetric method, the protein content test used the kjeldahl method, the fat content test used the soxlet method, while the carbohydrate content test used the by difference method. The results of the research showed that the water content, ash content, protein content, fat content and carbohydrate content of the black sea cucumber (Holothuria edulis) were respectively: 10.44%, 17.797%, 54.931%, 1.265%, 26%, while the water content, ash content, protein content, fat content and carbohydrate content of the sand sea cucumber (Holothuria scraba) were respectively: 9.559%, 34.134%, 32.644%, 0.23% and 32.961. ABSTRAKTeripang merupakan salah satu jenis hewan berkulit duri (Echinodermata). Duri pada teripang merupakan rangka atau skelet yang tersusun dari zat kapur dan terdapat di dalam kulitnya. Terdapat sekitar 1.250 jenis teripang yang telah didiskripsikan oleh para taksonomi. Penelitian ini bertujuan untuk mengetahui kandungan gizi teripang pasir (Holothuria scabra) dan teripang hitam (Holothuria edulis) di Perairan pantai Pura Agung Weri, Kabupaten Flores Timur. Penelitian dilaksanakan di ruang pengolahan Teknologi Hasil Perikanan Institut Keguruan dan Teknologi Larantuka, selanjutnya dilakukan analisis kandungan gizi teripang hitam (Holothuria edulis) dan teripang) pasir (Holothuria scraba) yang meliputi kadar air, kadar abu, protein, lemak, karbohidrat di laboratorium Kimia Pakan Fakultas Pertenakan dan Kelautan di UNDANA. Uji kadar air dan kadar abu menggunakan metode gravimetri, uji kadar protein menggunakan metode kjeldahl, uji kadar lemak menggunakan metode soxlet, sedangkan uji kadar karbohidrat menggunakan metode by difference. Hasil penelitian penelitian menujukan kadar air, kadar abu, kadar protein, kadar lemak dan karbohidrat dari teripang hitam (Holothuria edulis) berturut-turut: 10,44%, 17,797%, 54,931%, 1,265%, 26%, sedangkan kadar air, kadar abu, kadar protein, kadar lemak dan karbohidrat dari teripang pasir (Holothuria scraba) berturut turut: 9,559%, 34,134%, 32,644%, 0,23% dan 32,96.